The Impact of Incubators on the Success of Innovative Agribusinesses Founded by Youths in Cameroon - Parish, Diombai Rodet; Razack, Adeoti; Mignouna, Djana Babatima; Zozo, Nkoulou Nkoulou; Gbede, Rémy Tankpinou; Bamba, Zoumana; Abdoulaye, Tahirou; Manyong, Victor (European Scientific Journal, ESJ, 2023)
Entrepreneurship is a credible option for countries that aim to solve the problem of youth employability by supporting them. Therefore, the relevance of support structures such as incubators in an agricultural developing country like Cameroon is still relevant, and the analysis of their impact is necessary to the relevance and effectiveness of their action. The objective of this article is to analyze the impact of incubators in the agricultural sector, on the success of incubated firms by analyzing the direct impact of accessing the proposed services on the performance (development and growth) of incubated firms; we started from the Service-Dominant Logic to analyze the value of the proposed services from the point of view of the incubates. We mainly used the PLS method and found that incubators through their services (infrastructure, training and coaching, consulting and assistance, and networking) have an impact on the development (management, strategic alliances, innovation development) and growth (employment and wealth) of agribusinesses founded by young people. However, this impact is somewhat weak.